Are Salivary and Plasma Levels of Toll-Like Receptors 2 and 4 Elevated in Subjects With Chronic Periodontitis?: A Systematic Review and Meta-Analysis - Mario Alberto Alarcón-Sánchez; Ruth Rodríguez-Montaño; Sarah Monserrat Lomelí-Martínez; Cristina Hermila Martínez-Bugarin; Seyed Ali Mosaddad; Artak Heboyan (International Journal of Inflammation)
Toll-like receptors (TLR2 and TLR4) are crucial in the detection of pathogen-associated molecular patterns (PAMPs) during periodontitis, resulting in exacerbated production of proinflammatory cytokines and ultimately tissue damage and bone loss associated with this periodontal disease. This systematic review and meta-analysis aimed to systematically analyze and quantify the differences between TLR2 and TLR4 levels in the saliva and plasma of individuals with chronic periodontitis (CP) and systemically and periodontally healthy subjects (SPHS). The databases consulted were Scopus, Web of Science, and PubMed from 2011 to 2024 to locate cross-sectional studies that measured TLR2 and TLR4 levels. Studies selected were human research articles published in English, evaluating these biomarkers through ELISA. Data were extracted, and the quality of studies was appraised using the Joanna Briggs Institute (JBI) tool for observational studies. Meta-analyses were executed using STATA V.15 (StataCorp LP, College Station, Texas) employing fixed or random-effects models based on the degree of heterogeneity using I2 statistics. Out of 404 articles found, four studies were included for both qualitative and quantitative synthesis. We found an increase in salivary TLR4 levels in subjects with CP compared with SPHS (SMD = 265.217 (95% confidence interval (CI) = 109.311–421.122); p=0.001). As well as an increase in plasma levels of TLR4 in subjects with CP compared with SPHS (SMD = 2.93 (95% CI = 1.57–4.29); p=0.001). TLR4 concentrations in saliva and plasma of subjects with CP were higher than those observed in the healthy population. However, further validation in larger prospective studies is needed before clinical implementation.